Comparison of RT-PCR-Dot Blot Hybridization Based on Radioisotope 32P with Conventional RT-PCR and Commericial ELISA Assays for Blood Screening of HIV-1 - Maria Lina Rosilawati; Andi Yasmon (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2011)
There are many commercial ELISA and rapid test kits that have been used for blood screening; however, the kits can give false positive and negative results. Therefore, RT-PCR (Reverse Transcription Polymerase Chain Reaction) - Dot Blot Hybridization based on radioisotope 32P (RDBR) method was developed in this research, to compare the method with the conventional RT-PCR and commercial ELISA Enzyme-Linked Immunosorbent Assay) kit. This method is efficient for screening of large blood specimens and surveillance study. Eighty seven samples were used and serum of the samples were tested by ELISA to detect HIV-1. The HIV-1 RNA genome was extracted from plasma samples and tested using the RT-PCR and RDBR methods. Of 87 samples that were tested, the rates of positive testing of the RT-PCR, the RDBR, and the ELISA were 71.26%, 74.71%, and 80.46%, respectively. The RDBR (a combination of RT-PCR and dot blot hybridization) was more sensitive than conventional RT-PCR by showing 3.45% in increase number of positive specimens. The results showed that of 9 samples (10.34%) were negative RDBR and positive ELISA, while 4 samples (4.60%) werenegative ELISA and positive RDBR. The two methods showed slightly difference in the results but further validation is still needed. However, RDBR has highpotential as an alternative method for screening of blood in large quantities when compared to method of conventional RT-PCR and ELISA.